Consensus on the standardization of terminology in thrombotic thrombocytopenic purpura and related thrombotic microangiopathies. (30th January 2017) - Scully, M.; Cataland, S.; Coppo, P.; de la Rubia, J.; Friedman, K. D.; Kremer Hovinga, J.; Lämmle, B.; Matsumoto, M.; Pavenski, K.; Sadler, E.; Sarode, R.; Wu, H.; et al.
Abstract : Essentials An international collaboration provides a consensus for clinical definitions. This concerns thrombotic microangiopathies and thrombotic thrombocytopenic purpura (TTP). The consensus defines diagnosis, disease monitoring and response to treatment. Requirements for ADAMTS‐13 are given. Summary: Background: Thrombotic thrombocytopenic purpura (TTP) and hemolytic–uremic syndrome (HUS) are two important acute conditions to diagnose. Thrombotic microangiopathy (TMA) is a broad pathophysiologic process that leads to microangiopathic hemolytic anemia and thrombocytopenia, and involves capillary and small‐vessel platelet aggregates. The most common cause is disseminated intravascular coagulation, which may be differentiated by abnormal coagulation. Clinically, a number of conditions present with microangiopathic hemolytic anemia and thrombocytopenia, including cancer, infection, transplantation, drug use, autoimmune disease, and pre‐eclampsia and hemolysis, elevated liver enzymes and low platelet count syndrome in pregnancy. Despite overlapping clinical presentations, TTP and HUS have distinct pathophysiologies and treatment pathways. Objectives: To present a consensus document from an International Working Group on TTP and associated thrombotic microangiopathies (TMAs). Methods: The International Working Group has proposed definitions and terminology based on published information and consensus‐based recommendations. Conclusion: The consensus aims to aid clinical decisions, but also future studies and trials, utilizing standardized definitions. It presents a classification of the causes of TMA, and criteria for clinical response, remission and relapse of congenital and immune‐mediated TTP.